Sensitivity of Staphylococcus aureus Isolated from Nasal and Throat of Pre-Clerkship Students to Antibiotics - Rahayu, Suci; Widiyanti, Dian; Arsyad, Muhammad (Universitas Muhammadiyah Yogyakarta, 2020)
Background: Cases of nosocomial infection are many caused by the bacteria ofÂ S.aureus. Bacteria infection caused by S.aureus may result in various skin and soft tissue infections. The infection may become difficult to treat if the strain ofÂ S.aureus responsible is the methicillin resistant strain or methicillin-resistant Staphylococcus aureus (MRSA). Currently there are two known types of MRSA: Hospital Acquired MRSA/HA-MRSA and Community Acquired MRSA/CA-MRSA. Transmission of the bacteria from one patient to another may be caused by unsterile medical equipment or from the hospital staff, especially pre-clinical students who will work in a hospital. The purpose of this study was to obtained the difference of bacteria colonisations S.aureus from nasal and throat swabs, and the sensitivity patterns of S.aureus when exposed to antibiotics (methicillin, vancomycin, imipenem, penicillin, ofloxacin, ciprofloxacin) and the prevalence of MRSA carriers and also to obtain an understanding of the characteristics of medical drug use through Islamic views. Metodes: This study used descriptive analysis method with samples taken from nasal and throat swabs applied to healthy pre-clinic student from Universitas YARSI. Statistical analysis using Mann-Whitney test in the program SPSS for windows. Results: The results bacteria colonisations S.aureus from nasal swabs was positive (23,3%), while from the throat sample was positive (10%). The results of statistical analysis (Sig. = 0.051 0.05) shows that there is no significant difference between the bacterial colonies of S.aureus originating from the nasal swabs and throat swabs of the pre-clinical students. From 60 samples a positive prevalence of (1.7%) was obtained for MRSA carriers. The result of the sensitivity test shows that the isolated sample of the bacteria S.aureus shows the highest sensitivity to the antibiotic imipenem and almost all the isolated samples show resistance to the antibiotic penicillin. Conclusion: There are more S.aureus bacteria colonies on nasal swabs compared to throat swabs. There was no significant difference between S.aureus bacteria colonization of nose and throat swabs in pre-clinical-students. The positive prevalence of MRSA carrier among pre-clinical-students of Yarsi University was (1.7%). In nasal swabs all isolates were still sensitive to the antibiotics methicillin, imipenem, ofloxacin and ciprofloxacin. But on the nasal swab there were three VISA isolates. In the throat swab, there was one MRSA isolate and one isolate that was resistant to ofloxacin. The inhibition zone of the highest sensitivity was obtained for imipenem antibiotics. Almost all isolates showed resistance to penicillin antibiotics. In Islamic medicine, drugs or antibiotics must not contain unclean and haram objects for human consumption.